Peningkatan Ketahanan Ekonomi Keluarga Melalui Pemberdayaan Ibu Rumah Tangga dalam Pemasaran dan Olahan Kerupuk Kulit Ikan di Kampung Bugis - Azizah, Wafid; Wardani, Kadek Devi Kalfika Anggria; Putri, Dewa Ayu Putu Adhiya Garini (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2022)
The problem that occurred in Serangan Village, precisely in Bugis Village, was the decline in family economic income caused by the Covid-19 Pandemic and this was a challenge for researchers to overcome the low family economic income and increase the entrepreneurial spirit of housewives in the area. Seeing from the potential of the surrounding environment that is dominant in marine products, therefore researchers have a program in the form of empowering housewives in processing and marketing a processed product in the form of fish skin crackers by utilizing digital marketing in situations like this. With this empowerment, it is hoped that it will be able to encourage housewives to help the family economy. The purpose of this empowerment is so that later researchers can provide new ideas about processing fish skin crackers and in marketing them. Where the target to be achieved is that housewives can help the family's economic resilience during the current pandemic. The results and outputs obtained by the researchers are that housewives are able to make innovations in terms of taste as well as packaging and marketing of fish skin crackers.